Reduced radiation exposure in the cardiac catheterization laboratory with a novel vertical radiation shield. Issue 1 (3rd December 2019) - Panetta, Carmelo J.; Galbraith, Erin M.; Yanavitski, Marat; Koller, Patrick K.; Shah, Binita; Iqbal, Sohah; Cigarroa, Joaquin E.; Gordon, Gregory; Rao, Sunil V.
Abstract: Objectives: Investigation of novel vertical radiation shield (VRS) in reducing operator radiation exposure. Background: Radiation exposure to the operator remains an occupational health hazard in the cardiac catheterization laboratory (CCL). Methods: A mannequin simulating an operator was placed near a computational phantom, simulating a patient. Measurement of dose equivalent and Air Kerma located the angle with the highest radiation, followed by a common magnification (8 in.) and comparison of horizontal radiation absorbing pads (HRAP) with or without VRS with two different: CCL, phantoms, and dosimeters. Physician exposure was subsequently measured prospectively with or without VRS during clinical procedures. Results: Dose equivalent and Air Kerma to the mannequin was highest at left anterior oblique (LAO)‐caudal angle ( p  < .005). Eight‐inch magnification increased mGray by 86.5% and μSv/min by 12.2% compared to 10‐in. ( p  < .005). Moving 40 cm from the access site lowered μSv/min by 30% ( p  < .005). With LAO‐caudal angle and 8‐in. magnification, VRS reduced μSv/min by 59%, ( p  < .005) in one CCL and μSv by 100% ( p = .016) in second CCL in addition to HRAP. Prospective study of 177 procedures with HRAP, found VRS lowered μSv by 41.9% (μSv: 15.2 ± 13.4 vs. 26.2 ± 31.4, p = .001) with no difference in mGray. The difference was significant after multivariate adjustment for specified variables ( p  < .001). Conclusions: Operator radiation exposure is significantly reduced utilizing a novel VRS, HRAP, and distance from the X‐ray tube, and consideration of lower magnification and avoiding LAO‐caudal angles to lower radiation for both operator and patient.